Plants and animals based medicines used by Koch-Rajbanshi of Bhadrapur, Jhapa district, Eastern Nepal - Khadka, Pramila; Yadav, Prakash Kumar (Nepalese Journal of Biosciences, 2018)
The present study documented the traditional uses of 49 plant species and 18 animal species as medicines by the ethnic Koch- Rajbanshi inhabiting Bhadrapur in Jhapa district of eastern Nepal. Among 49 medicinal plant species documented 27, 5, 5, and 12 were herbs, shrubs, climbers and trees respectively. Similarly, among 12 animal species, arthropods, pisces, reptiles, aves and mammals were represented by dissimilar numbers such as 6, 3, 3 and 2, respectively.